Implementasi Algoritma Apriori Dalam Menentukan Penjualan Mobil Yang Paling Diminati Pada Honda Permata Serpong - Anggraini, Dewi; Putri, Sukmawati Anggraeni; Utami, Lilyani Asri (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2020)
The development of information technology is growing rapidly so that it enters various fields, the need for fast, accurate and accurate information is needed. But the fact is that high information needs are not balanced by the presentation of adequate information. Business development and competition are increasingly complex because consumers are very perspective making business people have to be smart in reading situations. So that business people can make a prediction of consumer interest to be used as a prediction of the company in making a decision, and change a strategy that is most appropriate for consumers. Decision makers try to utilize the available data warehouse, this encourages the emergence of new branches of science to overcome the extraction of information in very large amounts of data. To find out which Honda cars are most in demand by consumers, Data Mining techniques are required using the Apriori Algorithm method, and supported by the Tanagra Application by examining sales data for 1 year. Data Mining is an amalgamation of data analysis techniques, while Apriori Algorithm is the most frequently used method because it is very simple, easy and most widely proposed by some researchers, because there are two parameters namely Support Value and Confidence Value. Then the prediction results of the study found that Honda's car sales that most demanded by consumers were Brio Satya, HRV, Mobillio, Jazz, and CRV